1996
DOI: 10.1021/es9600035
|View full text |Cite
|
Sign up to set email alerts
|

Grain-Size Distribution of Polychlorobiphenyls in Coastal Sediments

Abstract: Congener-specific analyses of PCBs in marine sediments were undertaken to gain a better understanding of the distribution of this class of contaminants in relation to the grain-size of sediments. Twenty PCB congeners, selected for their potential toxicity and/or for their occurrence in the environmental samples, were studied in five grainsize sediment fractions (from φ > 800 µm to φ < 15 µm) and in the vegetal fragment fraction collected by flotation. PCB content and distribution profiles were observed in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(31 citation statements)
references
References 32 publications
2
25
1
3
Order By: Relevance
“…Mineral grain size (content percentage of sand) analysis showed that the inner shelf (10% to 30%) was composed mostly of fine terrestrial matters, and the middle-outer shelf (N 30%) was composed of coarse-grained quartz and some biogenic carbonates . The correlation between high ∑ 24 PCBs and fine particles indicated that the deposition of PCBs is also heavily affected by grain size (Duan et al, 2013;Piérard et al, 1996).…”
Section: Spatial Distribution Of Pcbs and Tocmentioning
confidence: 99%
“…Mineral grain size (content percentage of sand) analysis showed that the inner shelf (10% to 30%) was composed mostly of fine terrestrial matters, and the middle-outer shelf (N 30%) was composed of coarse-grained quartz and some biogenic carbonates . The correlation between high ∑ 24 PCBs and fine particles indicated that the deposition of PCBs is also heavily affected by grain size (Duan et al, 2013;Piérard et al, 1996).…”
Section: Spatial Distribution Of Pcbs and Tocmentioning
confidence: 99%
“…According to Kuzyk et al (2010), C org availability dictates the PCB transport and fate, including entry into food webs or burial in sediments, and therefore changes in the organic system (terrestrial or aquatic) implies changes in the contaminant pathways. Additionally, many authors have reported an inverse relationship between particle size and PCB sediment concentrations (Pierard et al, 1996;Alkhatib and Weigand 2002;Zhang et al, 2007;Kuzyk et al, 2010;Nehyba et al, 2010) which is attributed to the fact that the greater surface area of the smaller particles also provides a larger area for the adsorption of C org (Zhang et al, 2007).…”
Section: Pcb Concentrations Sources and Trendsmentioning
confidence: 99%
“…direct uptake from water phase via epidermis organs or gill (bioconcentration) and via gastrointestinal tract from ingestion of either suspended particulate matter or from consumption of contaminated feed or known as bioaccumulation and biomagnification (Pierard et al, 1996). Further on, bioavailability of the contaminant in the environment Table 3.…”
Section: Resultsmentioning
confidence: 99%